2018
DOI: 10.1002/rcs.1970
|View full text |Cite
|
Sign up to set email alerts
|

Introducing robotic radical hysterectomy for stage 1bi cervical cancer—A prospective evaluation of clinical and economic outcomes in a single UK institution

Abstract: Background We have assessed the impact of introducing robotics for a stage 1b cervical cancer service on laparotomy rates, complications, and costs. Methods Data were collected prospectively from 90 consecutive patients who had a radical hysterectomy between 1 April 2010 and 31 December 2017. Results There were 37 women before the first robotic procedure and 53 after. The laparotomy rate reduced from 75% (9/12) in 2010 to 0% (0/18) in 2017. The length of stay reduced from 6 days (range 3‐39) to 3 days (range 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A meta‐analysis 78 assessing RAL for radical hysterectomy in cervical cancer concluded there were fewer complications for RAL compared with open surgery. One study 79 has demonstrated that the introduction of robotics in the UK resulted in a reduced number of open radical hysterectomies. As a result, the introduction of robotics for cervical cancer surgery has become widely accepted, not just for hysterectomy but also for trachelectomy with a large meta‐analysis 80 reporting from nine studies.…”
Section: Role Of Robotic Surgery In Gynaecological Cancermentioning
confidence: 99%
“…A meta‐analysis 78 assessing RAL for radical hysterectomy in cervical cancer concluded there were fewer complications for RAL compared with open surgery. One study 79 has demonstrated that the introduction of robotics in the UK resulted in a reduced number of open radical hysterectomies. As a result, the introduction of robotics for cervical cancer surgery has become widely accepted, not just for hysterectomy but also for trachelectomy with a large meta‐analysis 80 reporting from nine studies.…”
Section: Role Of Robotic Surgery In Gynaecological Cancermentioning
confidence: 99%
“…Of these articles, 59 did not meet the selection criteria and were excluded. After reviewing the full texts of the remaining 36 articles, we found 20 relevant studies [ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ], published between 2008 and 2019, suitable for inclusion in the meta-analysis. Eleven out of the 16 studies excluded from the final review had insufficient data regarding survival outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents the main characteristics of the 20 studies included in the final analysis. Their study design types were retrospective (n=12) [ 17 18 19 20 22 24 25 26 27 30 31 33 ], matched retrospective (n=2) [ 21 29 ], and prospective (n=6) [ 14 15 16 23 28 32 ]. The locations of these studies were Asia (n=8) [ 20 21 22 25 27 28 31 33 ], Europe (n=8) [ 17 18 19 23 26 29 30 32 ], and the USA (n=4) [ 14 15 16 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…No significant between-study heterogeneity was detected. [20,22,28], 5 prospective cohort studies [12,13,23,32,34], and 1 randomized controlled trial [30]. Five studies were conducted in North America [12,13,16,24,34], 10 in Europe [14,15,17,18,22,23,27,28,32,33], and 8 in Asia [19−21,25,26,29−31].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[20,22,28], 5 prospective cohort studies [12,13,23,32,34], and 1 randomized controlled trial [30]. Five studies were conducted in North America [12,13,16,24,34], 10 in Europe [14,15,17,18,22,23,27,28,32,33], and 8 in Asia [19−21,25,26,29−31]. The countries with the largest representation in this meta-analysis were Italy (n = 6, 26.1%) [17,22,23,27,28,33], the United States (n = 5, 21.7%) [12,13,16,24,34], and South Korea (n = 4, 17.4%) Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%